Determinant of Financial Performance for General Insurance Companies in Indonesia - Fanny Septina (LPPM Universitas BSI, 2022)
The study aims to explore the influence of the insurance company’s specific variables and macroeconomic factors on financial performance of general insurance companies in Indonesia. The insurance company’s spesific variables are proxied by the claims ratio, premium growth ratio and risk-based-capital ratio as well as macroeconomic variables by Gross Domestic Products (GDP) and inflation, financial performance are proxied by return on assets and return on equity. The research samples are 35 registered general insurance companies at Financial Services Authority (OJK) for the 2016-2019 periods. The research method is panel data regression analysis with three stages model estimation approach ; Chow-test, Hausman-test and Langrange Multiplier-test to estimate the proper regression model of the Common Effect Model, Fixed Effect Model or Random Effect Model. The most fit regression model analysis to be selected is Random Effect Model. The results shows that the claims ratio affects return on assets and return on equity significantly, the risk-based-capital ratio affects return on assets significantly, but not affects return on equity significantly. While the premium growth ratio, GDP and inflation not affects return on assets and return on equity signficantly.